Anthropology Without Informants Collected Works in Paleoanthropology by L.G. Freeman - Freeman, L. G. (University Press of Colorado, 2009)
"It is my sincere hope that this volume will be much read and reflected upon by new generations of American students of prehistoric archaeologists. Freeman's career is a model for long-term international collaboration, theoretical eclecticism, the centrality of field research, and the ability to 'dream big,' but with a commonsense approach to the record and its limitations." Lawrence Guy Straus, Journal of Anthropological Research